Diapers in war zones: ethnomedical factors in acute childhood gastroenteritis in Peshawar, Pakistan. - Saira H Zaidi; Carolyn Smith-Morris (PLoS ONE, 2015)
This article considers ethnomedical knowledge and practices among parents related to contraction of acute gastroenteritis among children in Peshawar, Pakistan. Research methods included analysis of the Emergency Pediatric Services' admission register, a structured interview administered to 47 parents of patients seen in the Khyber Medical College Teaching Hospital, semi-structured interviews of 12 staff, and four home visits among families with children treated at the hospital. The use of native research assistants and participant observation contributed to the reliability of the findings, though the ethnographic, home-visit sample is small. Our research indicated that infection rates are exacerbated in homes through two culturally salient practices and one socioeconomic condition. Various misconceptions propagate the recurrence or perserverance of acute gastroenteritis including assumptions about teething leading to poor knowledge of disease etiology, rehydration solutions leading to increased severity of disease, and diaper usage leading to the spread of disease. In our Discussion, we suggest how hospital structures of authority and gender hierarchy may impact hospital interactions, the flow of information, and its respective importance to the patient's parents leading to possible propagation of disease. These ethnographic data offer a relatively brief but targeted course of action to improve the effectiveness of prevention and treatment efforts.